Analysis of Nutritional Status and The Incidence of Pulmonary Tuberculosis in The Puskesmas Martapura 1 - Aulia Ramadhani; Yustin Ari Prihandini; Lisa Setia; Nafila Nafila; Adies Riyana (Jurnal Berkala Kesehatan, 2024)
Tuberculosis (TB) is an infectious disease caused by bacteria and transmitted through the air. Indonesia, especially South Kalimantan, records a high number of TB cases. Martapura 1 Community Health Center, which is known for its significant number of pulmonary TB cases, requires special strategies in handling and prevention. This descriptive research uses a cross-sectional design. The research was carried out from February to June 2024, at Martapura 1 Health Center, Banjar Regency, South Kalimantan. The sample size was 50 people, with the sampling method being Accidental Sampling. Data collection techniques include BTA examination and BMI (Body Mass Index) assessment. Analysis of the relationship between nutritional status and the incidence of pulmonary TB in the working area of Martapura 1 Community Health Center, Banjar Regency, South Kalimantan based on statistical tests with chi-square obtained a p-value of 0.006 (p-value <0.05). Therefore, it can be concluded that there is a relationship between nutritional status and the incidence of pulmonary TB in the working area of Martapura 1 Health Center, Banjar Regency, South Kalimantan in 2024. The incidence of pulmonary TB can affect a person's nutritional status.